Newly isolated Bacillus clausii GMBAE 42: an alkaline protease producer capable to grow under higly alkaline conditions - KAZAN, DİLEK (WILEY, 2004)
Aim: The isolation and identification of new Bacillus sp. capable of growing under highly alkaline conditions as alkaline protease producers. Methods and Results: A Bacillus strain capable of growing under highly alkaline conditions was isolated from compost. The strain is a Gram-positive, spore-forming, motile, aerobic, catalase- and oxidase-positive, alkaliphilic bacterium and designated as GMBAE 42. Good growth of the strain was observed at pH 10. The strain was identified as Bacillus clausii according to the physiological properties, cellular fatty acid composition, G + C content of genomic DNA and 16S rRNA gene sequence analyses. The result of 16S rRNA sequence analyses placed this bacterium in a cluster with B. clausii. The G + C content of the genomic DNA of the isolate GMBAE 42 was found to be 49 mol%. The crude extracellular alkaline protease produced by the isolate showed maximal activity at pH 11.0 and 60degreesC. Conclusions: The results suggest that isolated strain GMBAE 42 is a new type of B. clausii capable of growing at pH 10.0 and produce extracellular alkaline protease very active at pH 11.0. Significance and Impact of the Study: Isolated strain could be used in commercial alkaline protease production and its enzyme can be considered as a candidate as an additive for commercial detergents.
Keywords: alkaline protease; Bacillus clausii; G plus C content; phenotypic characterization; phylogeny 16S rRNA; ALKALIPHILIC BACILLUS; SERINE-PROTEASE; STRAINS; REIDENTIFICATION; PURIFICATION; ALIGNMENT